Factors associated with depression among adults patients attending Daveyton main clinic, Ekurhuleni health district, Gauteng, South Africa - Mpangula, Ndaye Michel (My University, 2016)
Introduction: Major depression disorder (MDD) is a disabling disease, if diagnosed and treated in time its course can be changed and the patient’s quality of life can be restored. To our knowledge, no research has been conducted in primary care in Daveyton, South Africa to assess the profile of patients living with this disease. Against this background, this study aimed to assess factors associated with MDD among adult patients attending the Daveyton Main Clinic in Ekurhuleni in South Africa. Methodology: A cross-sectional study was conducted among 278 participants aged 18 and above. A patient health questionnaire (PHQ-9) including socio-demographic questions was used to gather participants’ information. The variables measured were: MDD prevalence, socio-demographics (age, gender, level of education, marital status, and employment status) of respondents who met diagnostic criteria for MDD, and participants’ co-morbid medical chronic conditions. Data capture was done using Excel, and analysis was done using the Statistical Packages for Social Sciences (SPSS) version 13. Demographic factors of participants are described in pie chart format, except for age, which is described in a table format with mean and standard deviation. Secondly, co-morbid medical conditions are described in table format. The association of MDD and the participants’ measured variable was examined using cross-tabulation, and it was tested using the chi-square test of independency. Results: The prevalence of MDD was 23%. The socio-demographic assessment revealed that: 22% of male were depressed versus 23.4% of female (p-value=0.8); 24.5% of single participants versus 18.9% of married participants (p-value=0.07); 10.5% of respondents without formal schooling, 29.4% of primary school educated respondents, 20.9% of high school educated respondents, and 34.2% of college graduates were depressed (p-value=0.1); 15.5% of employed participants versus 27.4% of unemployed participants were depressed (p-value= 0.02); and 14.7% of participants living with chronic co-morbid medical conditions were depressed (p-value=0.00). Conclusion: MDD was common in Daveyton Main Clinic. Patients living with chronic co-morbid diseases and those who were unemployed were more likely to have MDD. Health care workers must routinely carry out active screening for MDD in primary care patients.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Medicine in Family Medicine (M. Med in Fam. Med)